Study on nodal metastasis in neck (Bangladesh Journal of Otorhinolaryngology, 2009)
A cross sectional study was done in ENT Department, BSMMU from October 07 to March 08. An attempt has been made to evaluate metastatic neck node clinically. 60 cases were studied. Primary lesion identified in 53 cases (88.33%) and remain undetected in 7 cases (11.67%). Among primary sixty (60) diseases, 43 (81.13%) arises from upper aerodigestive tract which were squamous cell carcinoma & 10 (18.87%) came from thyroid & parotid gland. Commonest primary site was Larynx (36.67%). Majority (55%) of patients were age group 41-60. Unilateral lymph node was involved in 49 cases (81.67%), bilateral in 10 (16.67%), contra lateral in 1 case (1.66%), Single node in 22 (36.67%), Multiple in 38 (63.33%) cases. Size of the node >6cm was found in 24 cases (40%), 3-6cm in 20 cases (63.33%),